2002
DOI: 10.1088/0954-3899/28/6/303
|View full text |Cite
|
Sign up to set email alerts
|

Unitarity constraints on the stabilized Randall$ndash$Sundrum scenario

Abstract: Recently proposed stabilization mechanism of the Randall-Sundrum metric gives rise to a scalar radion, which couples universally to matter with a weak interaction ( ≃ 1 TeV) scale. Demanding that gauge boson scattering as described by the effective low enerrgy theory be unitary upto a given scale leads to significant constraints on the mass of such a radion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…To find when the perturbative approach breaks, it is customary (see, e.g., [21][22][23]) to study the perturbative unitarity of the scatterings between SM bosons mediated by the radion. The main constraint comes from W bosons scatterings, for which perturbative unitarity is maintained as long as [22] .…”
Section: A the Dfgk Modelmentioning
confidence: 99%
“…To find when the perturbative approach breaks, it is customary (see, e.g., [21][22][23]) to study the perturbative unitarity of the scatterings between SM bosons mediated by the radion. The main constraint comes from W bosons scatterings, for which perturbative unitarity is maintained as long as [22] .…”
Section: A the Dfgk Modelmentioning
confidence: 99%
“…With the presence of another scalar in the theory with couplings similar to those of the Higgs boson, it becomes important to inquire if it ruins the perturbative unitarity of the theory. In fact, a lot of work has been done in this aspect of the radion [38][39][40][41], and it can be concluded that the contribution of a light radion with Λ φ ∈ ½1∶5 TeV to the amplitudes of these processes are subleading, and hence highenergy behavior is majorly decided by the SM Higgs boson. (ii) Electroweak precision data.-The oblique parameters can be a useful way to constrain the effects of new physics, especially when the energy scale involved is close to m Z=W .…”
Section: Theoretical and Experimental Constraintsmentioning
confidence: 99%
“…In fact, a lot of work has been done in this aspect of the radion [34][35][36][37] and it can be concluded that the contribution of a light radion with Λ ϕ ∈ [1 : 5] TeV to the amplitudes of these processes are subleading and hence high energy behaviour is majorly decided by the SM higgs boson.…”
Section: Theoretical and Experimental Constraintsmentioning
confidence: 99%